Herbal Medicine for Slowing Aging and Aging-associated Conditions: Efficacy, Mechanisms and Safety - Phu, Hoa T.; Thuan, Duong T.B.; Nguyen, Thi H.D.; Posadino, Anna M.; Eid, Ali H.; Pintus, Gianfranco (Current Vascular Pharmacology, 2020)
Aging and aging-associated diseases are issues with unsatisfactory answers in the medical field. Aging causes important physical changes which, even in the absence of the usual risk factors, render the cardiovascular system prone to some diseases. Although aging cannot be prevented, slowing down the rate of aging is entirely possible to achieve. In some traditional medicine, medicinal herbs such as Ginseng, Radix Astragali, Ganoderma lucidum, Ginkgo biloba, and Gynostemma pentaphyllum are recognized by the “nourishing of life” and their role as anti-aging phytotherapeutics is increasingly gaining attention. By mainly employing PubMed here we identify and critically analysed 30 years of published studies focusing on the above herbs' active components against aging and aging-associated conditions. Although many plant-based compounds appear to exert an anti-aging effect, the most effective resulted in being flavonoids, terpenoids, saponins, and polysaccharides, which include astragaloside, ginkgolide, ginsenoside, and gypenoside specifically covered in this review. Their effects as antiaging factors, improvers of cognitive impairments, and reducers of cardiovascular risks are described, as well as the molecular mechanisms underlying the above-mentioned effects along with their potential safety. Telomere and telomerase, PPAR-α, GLUTs, FOXO1, caspase-3, bcl-2, along with SIRT1/AMPK, PI3K/Akt, NF-ΚB, and insulin/insulin-like growth factor-1 pathways appear to be their preferential targets. Moreover, their ability to work as antioxidants and to improve the resistance to DNA damage is also discussed. Although our literature review indicates that these traditional herbal medicines are safe, tolerable, and free of toxic effects, additional well-designed, large-scale randomized control trials need to be performed to evaluate short- and long-term effects and efficacy of these medicinal herbs.
Keywords: elderly